C++ essentials - Mueller, John 1958- (John Wiley & Sons, Inc., 2025)
The quick and crystal-clear guide to C++ programming C++ Essentials For Dummies is your useful reference to the key concepts of C++, the popular general-purpose language utilized everywhere from building games to writing parts of operating systems. With minimal review and background material--and absolutely no fluff--this book gets straight to the essential topics you need to know to ramp up, brush up, or level up. Get a helpful intro to the basic concepts of coding in C++ Review what you already know or pick up essential new skills Create projects that run smoothly with the C++ language Keep this concise reference book handy for jogging your memory as you work Great for supplementing classroom learning, reviewing for a certification, or staying knowledgeable on the job, C++ Essentials For Dummies is a fantastic refresher guide that you can always turn to for answers.
Includes index
Keywords: C++ (Computer program language); Computer programming; C++ (Langage de programmation); Programmation (Informatique); computer programming